Sistem Penunjang Keputusan Pra Rancang Bangun Industri Intermediate Minyak Pala - Muhamad Malik Gunawan; Marimin Marimin (School of Business, Bogor Agricultural University (SB-IPB), 2004)
A lot of industries such as pharmacy, food industry, cosmetics industries use nurmeg oil for their products. Demand of nutmeg oil is very high its abaut 3-4% every year. Indonesia can export nutmeg oil up to 75 % world demands. Nutmeg oil which was expoted by Indonesia was crude nutmeg oil how ever some times have inconsistency quality. In order to produce nutmeg oil with better quality, nutmeg oil intermediate industry is needed. Decision support system is used to suggest the most potential process based on expert opinions. Methodology used was system approach and it was support with Analytical Hierarchy Process (AHP), Exponencial Comparison Method (MPE) and financial feasibility analysis. The system was named SPKIMPA. This system consist four models there are selection model, election model, Institution model and financial feasibility model. From verification result it was know that the most potential process was fractionation. The intermediate industry is feasible to run with Net Present Value (NPV) value Rp 426.627.432,83,- and Internal Rate Return (IRR) value 45.28 %. Another result from verification system was created partnership with upperstream industry and also with downstream industry.